Evaluasi Website Dinas Cipta Karya Dan Tata Ruang Kabupaten Malang Menggunakan Pendekatan Human Centered Design (HCD) - Andy Jaya Hartanto; Ari Kusyanti; Retno Indah Rokhmawati (Jurnal Pengembangan Teknologi Informasi dan Ilmu Komputer, 2018)
Dinas Cipta Karya and Tata Ruang Kabupaten Malang (DCKTR) is a local service that has a useful website to provide information. There is a problem where the local service has difficulty in improving their website design. This problem has not been resolved in the absence of appropriate inputs and no evaluation to improve the website. An interface evaluation is required to optimize the use of the DCKTR website as media communication and information. To make this happen, DCKTR took the initiative to commit a website evaluation for interface optimization. Evaluation using Human Centered Design approach. The result of the prototyping from the DCKTR input will be compared and evaluate with the current website using a questionnaire and usability test. In addition, This research produces clickable prototype products, as well as recommendations derived from the usability problems of the existing evaluation data analysis.